Magnetic field effect on the binding energy of a hydrogenic impurity in GaAs-Ga₁₋xAlxAs superlattice - Abouelaoualim, D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The binding energy of shallow hydrogenic impurity in GaAs-GaAs-Ga₁₋xAlxAs superlattices, under the influence of magnetic field, is theoretically studied following a variational procedure within the effective-mass approximation and the new analytic wave function of superlattice. The binding energy is calculed and analyzed for various applied magnetic field, different impurity position and superlattice with different widths. The result show that the impurity binding energy depends strongly on the impurity position and magnetic field. It is also found that for impurities located at the center of the quantum wells of superlattices the binding energy always increases with the applied magnetic field.